2020
DOI: 10.1038/s41467-020-18379-8
|View full text |Cite
|
Sign up to set email alerts
|

Intercalated disc protein Xinβ is required for Hippo-YAP signaling in the heart

Abstract: Intercalated discs (ICD), specific cell-to-cell contacts that connect adjacent cardiomyocytes, ensure mechanical and electrochemical coupling during contraction of the heart. Mutations in genes encoding ICD components are linked to cardiovascular diseases. Here, we show that loss of Xinβ, a newly-identified component of ICDs, results in cardiomyocyte proliferation defects and cardiomyopathy. We uncovered a role for Xinβ in signaling via the Hippo-YAP pathway by recruiting NF2 to the ICD to modulate cardiac fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…Recently, we and others have shown that activating YAP in CMs suppressed the expression of inflammatory genes [16,42]. This study extended our understanding of YAP's role in cardiac homeostasis by systemically interrogating the relationship between YAP and cardiac TLR genes.…”
Section: Yap/tead1 Complex Is a Default Repressor Of Cardiomyocyte Tlr Genessupporting
confidence: 58%
“…Recently, we and others have shown that activating YAP in CMs suppressed the expression of inflammatory genes [16,42]. This study extended our understanding of YAP's role in cardiac homeostasis by systemically interrogating the relationship between YAP and cardiac TLR genes.…”
Section: Yap/tead1 Complex Is a Default Repressor Of Cardiomyocyte Tlr Genessupporting
confidence: 58%
“…Wnt signalling was found to be activated in cardiomyocytes which are involved in the fibrofatty replacement of cardiomyocytes in AC (Garcia-Gras et al, 2006). Similarly, the Hippo pathway was found to be controlled by molecules located at the ICD such as YAP (Chen et al, 2014;Guo et al, 2020;Vite et al, 2018). However, it is unclear whether these mechanisms regulate cardiomyocyte adhesion.…”
Section: Adhe S I On Of Interc Al Ated D Isc S Is Ti G Htly Reg Ul At...mentioning
confidence: 99%
“…Among all pathways investigated so far, best evidence has been collected that Wnt and the Hippo pathways are locally controlled at the ICD since YAP has been shown to interact with Pg and β‐catenin and to be regulated by α‐catenin as well (Chen et al, 2014; Vite et al, 2018). Moreover, Xinβ, a regulator of the Hippo pathway, was reported to localize to and thereby to recruit NF2 (Merlin) to ICD (Guo et al, 2020). However, this implies only that signalling molecules located at ICD control cardiomyocyte differentiation and cell fate which is disturbed during cardiac diseases.…”
Section: Adhesion Of Intercalated Discs Is Tightly Regulated By Signa...mentioning
confidence: 99%
“…We previously reported that Cypher/ZASP deficiency induced apoptosis, with a striking decrease in cell viability ( 12 ). Recent studies have linked other DCM-associated proteins, such as lamin and Xinβ, to cardiomyocyte proliferation ( 49 , 50 ). Moreover, Cypher interacted with β-catenin mainly through the PDZ domain ( Figures 4G–K ), thereby aligning with the finding that the PDZ domain of Shank3 is responsible for its interaction with β-catenin ( 51 ).…”
Section: Discussionmentioning
confidence: 99%